TRANSFERENCE AND COUNTERTRANSFERENCE IN COGNITIVE BEHAVIORAL THERAPY - Prasko, Jan; Diveky, Tomas; Grambal, Ales; Kamaradova, Dana; Mozny, Petr; Sigmundova, Zuzana; Slepecky, Milos; Vyskocilova, Jana (Biomedical papers, 2010)
Background: Both patients and psychotherapists can experience strong emotional reactions towards each other in what are termed transference and countertransference within therapy. In the first part of this review, we discuss transference issues. Although not usually part of the obvious language of cognitive behavioral therapy (CBT), examination of the cognitions related to the therapist, is an integral part of CBT, especially in working with difficult patients. In the second part, we cover counter-transference issues. We describe schematic issues that give rise to therapist counter-transference and explain how this interacts in different types of patient therapist encounter. We also examine ways in which the therapist can use CT to help him/her modify the countertransference and, in the process, assist the patient.Methods: PUBMED data base was searched for articles using the key words "therapeutic relations", "transference", "countertransference", "cognitive behavioral therapy", "cognitive therapy", "schema therapy", "dialectical behavioral therapy". The search was repeated by changing the key word. No language or time constraints were applied. The lists of references of articles detected by this computer data base search were examined manually to find additional articles. We also used the original texts of A. T. Beck, J. Beck, M. Linehan, R. Leahy, J. Young and others. Basically this is a review with conclusions about how therapists can manage transference issues.Results: Transference. The therapist should pay attention to negative or positive reactions towards him/ her but should not deliberately provoke or ignore them. He/she should be vigilant for signs of strong negative emotions, such as a disappointment, anger, and frustration experienced in the therapeutic relationship by the patient. Similarly he/ she should be alert to exaggerated positive emotions such as love, excessive idealization, praise or attempts to divert the attention of therapy onto the therapist. These reactions open space for understanding the patient's past and actual relations outside the therapy. Countertransference. The therapist should be aware of countertransference schemas as they apply to him/her. He/she should monitor his/her own feelings that indicate countertransference. Further, the assistance of and discussion with supervisors and colleagues is useful in regard to countertransference even in experienced therapists. Countertransference can be used as an open window into the interpersonal relations of the patient.Conclusions: Both the literature and our experience underscore the importance of careful and open examination of both transference and counter-transference issues in CBT and their necessary incorporation in the complete management of all patients undergoing CBT.
Keywords: Therapeutic relationship/Transference/Idealization/Disappointment/Anger/Countertransference/Schemas/Cognitive behavioural therapy/Interpersonal relations